Distribution of Spread and Characteristics of Confirmed Covid-19 based on Spatial Autocorrelation in Manado - Pontoh, Sophia Olga; Weku, Winsy; Hatidja, Djoni (Operations Research: International Conference Series, 2022)
Covid-19 is a collection of viruses that attack the respiratory system. This virus spread quickly and spread to other regions in China and most countries in the world, including Indonesia. North Sulawesi Province, especially Manado City is one of the cities in Indonesia that has been affected by Covid-19. The highest confirmed Covid-19 cases in Manado City are in the Malalayang, Mapanget, and Wanea villages which are geographically not adjacent/neighboring. This study aims to analyze the spatial distribution of Covid-19 cases and their characteristics. This study uses significant data on Covid-19 cases in every village in Manado City, where there are 86 villages (Malayang Satu Barat Village and Malalayang Satu Timur Village combined), and the focus of this research is on the confirmed variables, with the latest data update is October 21, 2021. The effect of covid-19 between observation locations is accomplished using Moran's I, and the weighting matrix used is the Euclidean distance matrix. The Moran's Index provides an overview of the spatial relevance of the Covid-19 case data in every village in Manado City and specifically the spatial attachment of every village will be explained by the Local Moran's I value (LISA). The results of this study found that there is a spatial autocorrelation found using the Euclidean distance matrix. A spatial correlogram of 30 meters is used as the maximum geographical distance limit for being infected with Covid-19. The Moran's Index value of the Covid-19 case in Manado City is 0.348, meaning that there is a positive autocorrelation between the villages. There are thirteen villages that affect the spread of Covid-19 in Manado City, namely Malalayang Satu Timur dan Barat, Malalayang Satu, Winangun Satu, Kleak, Karombasan Utara, Ranotana Weru, Bumi Nyiur, Pakowa, Tinkulu, Taas, Paal Empat, Tikala Baru, and Paniki Dua.